Pengaruh Literasi Ekonomi Dan Teman Sebaya Terhadap Perilaku Konsumtif Siswa Kelas Xi Ips Sma Jawaahirul Hikmah Besuki - Tulungagung Tahun Pelajaran 2020/2021 - Nur Lina; Imam Sukwatus Sujai (UNIVERSITAS PGRI TULUNGAGUNG, 2023)
This study aims to describe the influence of economic literacy and peers on the consumptive behavior of class XI Social Sciences students at SMA Jawaahirul Hikmah Besuki-Tulungagung for the academic year 2020/2021. This research method uses quantitative methods. The subjects of this research are all students of class XI Social Sciences SMA Jawaahirul Hikmah Besuki-Tulungagung Academic Year 2020/2021 with a population of 65 students with a sample of 56 students. The data collection method used a questionnaire / questionnaire that was tested for validity and reliability. Data analysis used multiple linear regression analysis. The results of this study indicate (1) there is a significant influence between economic literacy and consumptive behavior partially with t count 2.163 t table 2.006 (2) there is a significant influence between peers and partial consumptive behavior with t count 2.832 t table 2.006 (3) there is a significant effect between economic literacy and peers on consumptive behavior simultaneously with F count 14.424 F table 3.17. The results of the regression equation Y = 21.410 + 0.303X1 + 0.372X2.